A biodegradable multilayer polymer foam material and its preparation method

By forming chemical crosslinking points between modified epoxy barrier agents and PBAT/PLA, the compatibility and melt strength issues of the PBAT/PLA blend system were resolved, resulting in the preparation of a multilayer biodegradable foam material with excellent mechanical and barrier properties.

CN120773427BActive Publication Date: 2025-11-14SHENZHEN HONGCAI NEW MATERIAL TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511277104.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-09
Publication Date
2025-11-14
Estimated Expiration
2045-09-09

AI Technical Summary

Technical Problem

Existing PBAT/PLA blend systems suffer from poor compatibility, low melt strength, and difficulty in controlling cell structure during the foaming process, resulting in insufficient mechanical and barrier properties and making it difficult to prepare high-performance biodegradable foamed materials.

Method used

Modified epoxy barrier agents are used. The modified epoxy barrier agents prepared by esterification and ring-opening reaction form chemical crosslinking points with PBAT and PLA to enhance interfacial adhesion. The melt strength and barrier performance are improved by hexa-boron ester and triazine ring. A multilayer structure is designed to give full play to the function of each layer.

Benefits of technology

It significantly improves the mechanical and barrier properties of multilayer polymer foam materials while maintaining biodegradability, with a uniform and dense cell structure and excellent overall material performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120773427B_ABST
    Figure CN120773427B_ABST
Patent Text Reader

Abstract

This invention discloses a biodegradable multilayer polymer foam material and its preparation method, belonging to the technical field of multilayer polymer foam materials. The biodegradable multilayer polymer foam material prepared by this invention comprises an upper surface layer, a lower surface layer, and a core layer disposed between the upper and lower surface layers. The upper and lower surface layers comprise the following components in parts by weight: 50-80 parts PBAT, 20-50 parts PLA, 3-8 parts foaming agent, 5-15 parts modified epoxy barrier agent, 0.5-2 parts epoxy chain extender, 1-5 parts calcium silicate, 3-10 parts montmorillonite, 0.5-2 parts lubricant, and 0.2-1 parts antioxidant. The core layer comprises the following components in parts by weight: 40-70 parts PBAT, 30-60 parts PLA, 5-12 parts foaming agent, 0.5-2 parts epoxy chain extender, 1-5 parts calcium silicate, 3-10 parts montmorillonite, 0.5-3 parts talc, 0.5-2 parts lubricant, and 0.2-1 parts antioxidant. This multilayer polymer foam material fully utilizes the functional characteristics of each layer, giving the material as a whole excellent mechanical properties, cell structure, degradation performance, and significant barrier properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of multilayer polymer foam materials technology, and particularly relates to a biodegradable multilayer polymer foam material and its preparation method. Background Technology

[0002] Polymer foam materials, such as expanded polystyrene (EPS) and expanded polypropylene (EPP), are widely used in packaging, construction, and catering due to their excellent properties such as light weight, thermal insulation, cushioning, and low cost. However, most traditional polymer foam materials use non-renewable petroleum-based plastics as raw materials. These materials are chemically stable and difficult to degrade in the natural environment. Improper disposal of their waste can cause serious white pollution and microplastic problems, placing enormous pressure on the ecological environment. With increasing global environmental awareness, the development of environmentally friendly, biodegradable polymer foam materials has become an urgent need and an important development direction for the industry.

[0003] Among numerous biodegradable polymers, polybutylene adipate / terephthalate (PBAT) and polylactic acid (PLA) are considered two of the most promising materials. PBAT is an aliphatic-aromatic copolyester with excellent flexibility and film-forming properties. Its processing performance is similar to that of low-density polyethylene (LDPE), and it can be completely degraded under composting conditions. However, PBAT also has significant drawbacks: its low crystallinity leads to insufficient strength and modulus, resulting in poor support when used as a foaming material; more importantly, its low melt strength and poor melt viscoelasticity prevent it from effectively encapsulating gas during foaming, causing bubble walls to easily rupture and making it difficult to form a uniform and fine cell structure. Typically, only foam products with large or uneven cells can be obtained, severely limiting its application in high-performance foaming fields.

[0004] Polylactic acid (PLA) is a polyester derived from renewable plants such as corn and cassava. It possesses high strength, modulus, and good rigidity, and its degradation products are carbon dioxide and water, making it environmentally friendly. Theoretically, blending PLA with PBAT can complement each other's advantages: PLA provides rigid support, while PBAT provides flexibility, resulting in a biodegradable foam material with excellent overall performance. However, unfortunately, because PBAT is an aromatic-aliphatic polyester and PLA is a rigid-chain polyester, the two are thermodynamically incompatible, resulting in weak interfacial adhesion. Simple blending easily leads to phase separation, causing defects at the blend interface. This incompatibility further deteriorates the melt strength of the blend system, making the interface a stress concentration point during foaming, more prone to cell coalescence and collapse, making the cell structure difficult to control, and the final product's mechanical properties usually lower than expected.

[0005] Currently, to improve the compatibility and foaming properties of PBAT / PLA blends, researchers typically add compatibilizers or chain extenders. For example, epoxy chain extenders are used to increase melt strength, or reactive compatibilizers are used to improve interfacial adhesion. However, these conventional methods often only address melt strength or compatibility issues individually, with limited effectiveness and little improvement in the material's gas barrier properties. Therefore, developing a multifunctional additive that can simultaneously and effectively improve PBAT / PLA compatibility, significantly increase its melt strength, and impart excellent barrier properties, and applying it to multilayer structure design, is crucial for preparing high-performance biodegradable polymer foam materials. Summary of the Invention

[0006] In order to overcome the shortcomings of the prior art, the present invention applies a modified epoxy barrier agent to the surface layer, so that a network with strong intermolecular forces and a dense structure can be formed on the surface of the foamed material. This not only greatly improves the foaming quality and significantly enhances the mechanical and barrier properties of the material, but also ensures the overall biodegradability of the material.

[0007] To achieve the above objectives, the following technical solution is adopted: On the one hand, the present invention provides a biodegradable multilayer polymer foam material, comprising an upper surface layer, a lower surface layer, and a core layer disposed between the upper surface layer and the lower surface layer. The upper surface layer and the lower surface layer comprise the following components in parts by weight: 50-80 parts PBAT, 20-50 parts PLA, 3-8 parts foaming agent, 5-15 parts modified epoxy barrier agent, 0.5-2 parts epoxy chain extender, 1-5 parts calcium silicate, 3-10 parts montmorillonite, 0.5-2 parts lubricant, and 0.2-1 parts antioxidant.

[0008] The core layer comprises the following components in parts by weight: 40-70 parts PBAT, 30-60 parts PLA, 5-12 parts foaming agent, 0.5-2 parts epoxy chain extender, 1-5 parts calcium silicate, 3-10 parts montmorillonite, 0.5-3 parts talc, 0.5-2 parts lubricant, and 0.2-1 parts antioxidant;

[0009] Furthermore, the modified epoxy barrier agent is prepared through the following steps:

[0010] (1) Add 2-[(4,6-diamino-1,3,5-triazine-2-yl)amino]propane-1,3-diol and dry N,N-dimethylformamide to the reactor and stir until completely dissolved. Slowly add (4-(cyclopropanesulfonamide)phenyl)boric acid and catalyst a under a nitrogen atmosphere. Heat to 75-85℃ and react for 5-8 hours. After the reaction is complete, cool the mixture to room temperature, pour it into ice water to precipitate the precipitate, filter, wash the precipitate with water, and dry it under vacuum to obtain the intermediate. (2) Add the intermediate and dry dimethyl sulfoxide to the reactor and stir to dissolve. Add excess diethylene glycol diglycidyl ether and stir to mix evenly. Add catalyst b. Heat to 90-100℃ and react for 7-9 hours. After the reaction is complete, cool the reaction solution to 45-55℃, add ethanol to precipitate the product, filter, wash with ethanol, and dry under vacuum to obtain the modified epoxy barrier agent.

[0011] The reaction formula for the preparation process of the modified epoxy barrier agent is as follows:

[0012]

[0013] The preparation of 2-[(4,6-diamino-1,3,5-triazine-2-yl)amino]propane-1,3-diol is based on European Patent Publication No. EP2774922A1, and is obtained by reacting melamine with serine.

[0014] Further, in step (1), the molar ratio of 2-[(4,6-diamino-1,3,5-triazine-2-yl)amino]propane-1,3-diol to (4-(cyclopropanesulfonamide)phenyl)boronic acid is 1:0.95-1.05.

[0015] Further, catalyst a is one of p-toluenesulfonic acid, camphorsulfonic acid, or tetraisopropoxytitanium, and its addition amount is 0.5%-2% of the total mass of the reactants.

[0016] Furthermore, in step (2), the molar ratio of diethylene glycol diglycidyl ether to the intermediate is 2.2-2.8:1.

[0017] Furthermore, the catalyst b is one of triphenylphosphine, triethylamine or benzyltriethylammonium chloride, and its addition amount is 1%-3% of the mass of the intermediate.

[0018] Furthermore, the foaming agent is one of azodicarbonamide, sodium bicarbonate, or 4,4'-oxobis(benzenesulfonyl)hydrazine.

[0019] Furthermore, the lubricant is one of zinc stearate, calcium stearate, or polyethylene wax.

[0020] Furthermore, the epoxy chain extender is at least one of styrene-ethylene oxide copolymer, glycidyl methacrylate copolymer, or ethylene-methyl acrylate-glycidyl methacrylate terpolymer.

[0021] Furthermore, the antioxidant is at least one of antioxidant 1010, antioxidant 168, or antioxidant 1076.

[0022] On the other hand, the present invention also provides a method for preparing a biodegradable multilayer polymer foam material, comprising the following steps:

[0023] S1. The components of the surface layer and the core layer are premixed evenly in a high-speed mixer according to the proportions. Then, they are melt-blended, extruded, cooled, and pelletized separately through a twin-screw extruder at a processing temperature of 140-170℃ to obtain surface layer masterbatch and core layer masterbatch.

[0024] S2. Multilayer co-extrusion foaming: The surface masterbatch and core masterbatch are added to the corresponding hoppers of the three-layer co-extrusion foaming molding machine, wherein the upper and lower surface layers use surface masterbatch, and the core layer uses core masterbatch; the processing temperatures of each section are set as follows: Zone 1 150℃, Zone 2 160℃, Zone 3 165℃, and die head 170℃. After melt co-extrusion, foaming, shaping, traction, and cutting, the biodegradable multilayer polymer foam material is obtained.

[0025] The beneficial effects of this invention are:

[0026] The biodegradable multilayer polymer foam material prepared by this invention has an upper and lower surface layer composed of PBAT, PLA, foaming agent, modified epoxy barrier agent, epoxy chain extender, calcium silicate, montmorillonite, lubricant, antioxidant, etc., while the core layer is composed of PBAT, PLA, foaming agent, epoxy chain extender, calcium silicate, montmorillonite, talc, lubricant, antioxidant, etc. This multilayer polymer foam material fully utilizes the functional characteristics of each layer, giving the material as a whole excellent mechanical properties, cell structure, degradation performance, and significant barrier properties.

[0027] In the preparation of modified epoxy barrier agents, 2-[(4,6-diamino-1,3,5-triazine-2-yl)amino]propane-1,3-diol and (4-(cyclopropanesulfonamide)phenyl)boronic acid are first esterified to generate an intermediate containing a six-membered borate ester structure. The amino group on this intermediate further undergoes a ring-opening reaction with the epoxy group of diethylene glycol diglycidyl ether to finally obtain a molecule containing epoxy groups, hydroxyl groups, triazine rings, sulfonamide groups, and borate ester structures. During processing, the epoxy group can undergo chain extension reactions with the end groups of the polymer to increase the molecular weight, improve the melt strength, and produce a synergistic effect with the original epoxy chain extender in the system.

[0028] The sulfonamide group has high reactivity and can react with the end groups of PBAT and PLA molecular chains at processing temperatures to form chemical cross-linking points, further increasing the molecular weight and melt strength of the polymer. At the same time, the sulfonamide group has strong polarity and can form strong hydrogen bond interactions with the ester groups in the PBAT and PLA molecular chains, effectively improving the two-phase interface, reducing the phase separation size, and enhancing the interfacial adhesion. This makes the originally poorly compatible PBAT / PLA blend system more homogeneous and stable. The hydroxyl groups introduced by the reaction of the amino group on the intermediate with diethylene glycol diglycidyl ether can also form hydrogen bonds with other molecular chains, further enhancing the interfacial forces and the cohesive energy of the overall material.

[0029] The six-membered borate ester bond possesses dynamic and reversible properties, which can dissipate stress during processing, helping to improve the processing rheology of the blend. More importantly, the presence of the borate ester group can effectively hinder the permeation of small molecule gases, significantly improving the barrier properties of the material. The triazine ring, a nitrogen-rich rigid aromatic heterocyclic structure, inherently provides good mechanical strength and thermal stability. Multiple triazine rings can form physical crosslinking points through π-π stacking, further strengthening the polymer network, restricting molecular chain movement, and contributing to increased melt strength and the modulus of the final product, thus enhancing barrier properties. Attached Figure Description

[0030] Figure 1 These are schematic diagrams of the structures of the multilayer polymer foam materials in Examples 1-4 of the present invention;

[0031] Figure 2 The modified epoxy barrier agent prepared in Example 4 of this invention 1 HNMR image.

[0032] In the diagram: 1. Top layer; 2. Core layer; 3. Bottom layer.

[0033] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used together with the embodiments of the invention to explain the invention and do not constitute a limitation thereof. Detailed Implementation

[0034] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0035] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those familiar to those skilled in the art. Furthermore, any methods and materials similar to or equivalent to those described herein may be applied to this invention. The preferred embodiments and materials described herein are for illustrative purposes only and do not limit the scope of this application.

[0036] Unless otherwise specified, the experimental methods used in the following examples are conventional methods, and the experimental materials used in the following examples were all purchased from commercial sources. A schematic diagram of the structure of the multilayer polymer foam material in the following examples is shown below. Figure 1 .

[0037] Example 1: A biodegradable multilayer polymer foam material, comprising an upper surface layer 1, a lower surface layer 3, and a core layer 2 disposed between the upper surface layer 1 and the lower surface layer 3, wherein the upper surface layer 1 and the lower surface layer 3 comprise the following components in parts by weight: 50 parts PBAT, 20 parts PLA, 3 parts foaming agent, 5 parts modified epoxy barrier agent, 0.5 parts epoxy chain extender, 1 part calcium silicate, 3 parts montmorillonite, 0.5 parts lubricant, and 0.2 parts antioxidant;

[0038] The core layer 2 comprises the following components in parts by weight: 40 parts PBAT, 30 parts PLA, 5 parts foaming agent, 0.5 parts epoxy chain extender, 1 part calcium silicate, 3 parts montmorillonite, 0.5 parts talc, 0.5 parts lubricant, and 0.2 parts antioxidant.

[0039] The modified epoxy barrier agent is prepared through the following steps:

[0040] (1) Add 2-[(4,6-diamino-1,3,5-triazine-2-yl)amino]propane-1,3-diol and dry N,N-dimethylformamide to the reactor and stir until completely dissolved. Slowly add (4-(cyclopropanesulfonamide)phenyl)boric acid and catalyst a under a nitrogen atmosphere. Heat to 75°C and react for 5 hours. After the reaction is complete, cool the mixture to room temperature, pour it into ice water to precipitate, filter, wash the precipitate with water, and dry it under vacuum to obtain the intermediate.

[0041] (2) Add intermediate and dry dimethyl sulfoxide to the reactor, stir to dissolve, add excess diethylene glycol diglycidyl ether, stir to mix evenly, add catalyst b; heat to 90°C, react for 7 hours, after the reaction is completed, cool the reaction solution to 45°C, add ethanol to precipitate the product, filter, wash with ethanol, and obtain the modified epoxy barrier agent by vacuum drying.

[0042] In step (1), the molar ratio of 2-[(4,6-diamino-1,3,5-triazine-2-yl)amino]propane-1,3-diol to (4-(cyclopropanesulfonamide)phenyl)boronic acid is 1:0.95; catalyst a is p-toluenesulfonic acid, and its addition amount is 0.5% of the total mass of the reactants; in step (2), the molar ratio of diethylene glycol diglycidyl ether to the intermediate is 2.2:1; catalyst b is triphenylphosphine, and its addition amount is 1% of the mass of the intermediate.

[0043] The foaming agent is azodicarbonamide; the lubricant is zinc stearate; the epoxy chain extender is styrene-acrylate ethylene oxide copolymer; and the antioxidant is antioxidant 1010.

[0044] A method for preparing a biodegradable multilayer polymer foam material includes the following steps:

[0045] S1. The components of the surface layer and core layer 2 are premixed evenly in a high-speed mixer according to the proportions. Then, they are melt-blended, extruded, cooled, and pelletized by a twin-screw extruder at a processing temperature of 140°C to obtain the surface layer masterbatch and the core layer masterbatch.

[0046] S2. Multilayer co-extrusion foaming: The surface masterbatch and core masterbatch are added to the corresponding hoppers of the three-layer co-extrusion foaming molding machine, wherein the upper surface layer 1 and the lower surface layer 3 use surface masterbatch, and the core layer 2 uses core masterbatch; the processing temperatures of each section are set as follows: Zone 1 150℃, Zone 2 160℃, Zone 3 165℃, and die head 170℃. After melt co-extrusion, foaming, shaping, traction, and cutting, the biodegradable multilayer polymer foam material is obtained.

[0047] Example 2: A biodegradable multilayer polymer foam material, comprising an upper surface layer 1, a lower surface layer 3, and a core layer 2 disposed between the upper surface layer 1 and the lower surface layer 3, wherein the upper surface layer 1 and the lower surface layer 3 comprise the following components in parts by weight: 80 parts PBAT, 50 parts PLA, 8 parts foaming agent, 15 parts modified epoxy barrier agent, 2 parts epoxy chain extender, 5 parts calcium silicate, 10 parts montmorillonite, 2 parts lubricant, and 1 part antioxidant;

[0048] The core layer 2 comprises the following components in parts by weight: 70 parts PBAT, 60 parts PLA, 12 parts foaming agent, 2 parts epoxy chain extender, 5 parts calcium silicate, 10 parts montmorillonite, 3 parts talc, 2 parts lubricant, and 1 part antioxidant.

[0049] The modified epoxy barrier agent is prepared through the following steps:

[0050] (1) Add 2-[(4,6-diamino-1,3,5-triazine-2-yl)amino]propane-1,3-diol and dry N,N-dimethylformamide to the reactor and stir until completely dissolved. Slowly add (4-(cyclopropanesulfonamide)phenyl)boric acid and catalyst a under a nitrogen atmosphere. Heat to 85°C and react for 8 hours. After the reaction is complete, cool the mixture to room temperature, pour it into ice water to precipitate, filter, wash the precipitate with water, and dry it under vacuum to obtain the intermediate.

[0051] (2) Add intermediate and dry dimethyl sulfoxide to the reactor, stir to dissolve, add excess diethylene glycol diglycidyl ether, stir to mix evenly, add catalyst b; heat to 100℃, react for 9 hours, after the reaction is completed, cool the reaction solution to 55℃, add ethanol to precipitate the product, filter, wash with ethanol, and obtain the modified epoxy barrier agent by vacuum drying.

[0052] In step (1), the molar ratio of 2-[(4,6-diamino-1,3,5-triazine-2-yl)amino]propane-1,3-diol to (4-(cyclopropanesulfonamide)phenyl)boronic acid is 1:1.05; catalyst a is camphor sulfonic acid, and its addition amount is 2% of the total mass of the reactants; in step (2), the molar ratio of diethylene glycol diglycidyl ether to the intermediate is 2.8:1; catalyst b is triethylamine, and its addition amount is 3% of the mass of the intermediate.

[0053] The foaming agent is sodium bicarbonate; the lubricant is calcium stearate; the epoxy chain extender is glycidyl methacrylate copolymer; and the antioxidant is antioxidant 168.

[0054] A method for preparing a biodegradable multilayer polymer foam material includes the following steps:

[0055] S1. The components of the surface layer and core layer 2 are premixed evenly in a high-speed mixer according to the proportions. Then, they are melt-blended, extruded, cooled, and pelletized by a twin-screw extruder at a processing temperature of 170°C to obtain the surface layer masterbatch and the core layer masterbatch.

[0056] S2. Multilayer co-extrusion foaming: The surface masterbatch and core masterbatch are added to the corresponding hoppers of the three-layer co-extrusion foaming molding machine, wherein the upper surface layer 1 and the lower surface layer 3 use surface masterbatch, and the core layer 2 uses core masterbatch; the processing temperatures of each section are set as follows: Zone 1 150℃, Zone 2 160℃, Zone 3 165℃, and die head 170℃. After melt co-extrusion, foaming, shaping, traction, and cutting, the biodegradable multilayer polymer foam material is obtained.

[0057] Example 3: A biodegradable multilayer polymer foam material, comprising an upper surface layer 1, a lower surface layer 3, and a core layer 2 disposed between the upper surface layer 1 and the lower surface layer 3, wherein the upper surface layer 1 and the lower surface layer 3 comprise the following components in parts by weight: 60 parts PBAT, 40 parts PLA, 5 parts foaming agent, 10 parts modified epoxy barrier agent, 1.5 parts epoxy chain extender, 2 parts calcium silicate, 5 parts montmorillonite, 1.2 parts lubricant, and 0.5 parts antioxidant;

[0058] The core layer 2 comprises the following components in parts by weight: 50 parts PBAT, 45 parts PLA, 10 parts foaming agent, 1.5 parts epoxy chain extender, 2 parts calcium silicate, 5 parts montmorillonite, 2 parts talc, 1.2 parts lubricant, and 0.5 parts antioxidant.

[0059] The modified epoxy barrier agent is prepared through the following steps:

[0060] (1) Add 2-[(4,6-diamino-1,3,5-triazine-2-yl)amino]propane-1,3-diol and dry N,N-dimethylformamide to the reactor and stir until completely dissolved. Slowly add (4-(cyclopropanesulfonamide)phenyl)boric acid and catalyst a under a nitrogen atmosphere. Heat to 80°C and react for 6 hours. After the reaction is complete, cool the mixture to room temperature, pour it into ice water to precipitate, filter, wash the precipitate with water, and dry it under vacuum to obtain the intermediate.

[0061] (2) Add intermediate and dry dimethyl sulfoxide to the reactor, stir to dissolve, add excess diethylene glycol diglycidyl ether, stir to mix evenly, add catalyst b; heat to 95°C, react for 8 hours, after the reaction is completed, cool the reaction solution to 50°C, add ethanol to precipitate the product, filter, wash with ethanol, and obtain the modified epoxy barrier agent by vacuum drying.

[0062] In step (1), the molar ratio of 2-[(4,6-diamino-1,3,5-triazine-2-yl)amino]propane-1,3-diol to (4-(cyclopropanesulfonamide)phenyl)boronic acid is 1:1; catalyst a is tetraisopropoxytitanium, and its addition amount is 1.2% of the total mass of the reactants; in step (2), the molar ratio of diethylene glycol diglycidyl ether to the intermediate is 2.5:1; catalyst b is benzyltriethylammonium chloride, and its addition amount is 2% of the mass of the intermediate.

[0063] The foaming agent is 4,4'-oxobisbenzenesulfonyl hydrazine; the lubricant is polyethylene wax; the cyclohexene-methyl acrylate-glycidyl methacrylate terpolymer is used; and the antioxidant is antioxidant 1076.

[0064] A method for preparing a biodegradable multilayer polymer foam material includes the following steps:

[0065] S1. The components of the surface layer and core layer 2 are premixed evenly in a high-speed mixer according to the proportions. Then, they are melt-blended, extruded, cooled, and pelletized by a twin-screw extruder at a processing temperature of 150°C to obtain the surface layer masterbatch and the core layer masterbatch.

[0066] S2. Multilayer co-extrusion foaming: The surface masterbatch and core masterbatch are added to the corresponding hoppers of the three-layer co-extrusion foaming molding machine, wherein the upper surface layer 1 and the lower surface layer 3 use surface masterbatch, and the core layer 2 uses core masterbatch; the processing temperatures of each section are set as follows: Zone 1 150℃, Zone 2 160℃, Zone 3 165℃, and die head 170℃. After melt co-extrusion, foaming, shaping, traction, and cutting, the biodegradable multilayer polymer foam material is obtained.

[0067] Example 4: A biodegradable multilayer polymer foam material, comprising an upper surface layer 1, a lower surface layer 3, and a core layer 2 disposed between the upper surface layer 1 and the lower surface layer 3, wherein the upper surface layer 1 and the lower surface layer 3 comprise the following components in parts by weight: 60 parts PBAT, 40 parts PLA, 5 parts foaming agent, 10 parts modified epoxy barrier agent, 1.5 parts epoxy chain extender, 2 parts calcium silicate, 5 parts montmorillonite, 1.2 parts lubricant, and 0.5 parts antioxidant;

[0068] The core layer 2 comprises the following components in parts by weight: 50 parts PBAT, 45 parts PLA, 10 parts foaming agent, 1.5 parts epoxy chain extender, 2 parts calcium silicate, 5 parts montmorillonite, 1.5 parts talc, 1.2 parts lubricant, and 0.5 parts antioxidant.

[0069] The epoxy chain extender is obtained by combining styrene-ethylene acrylate copolymer, glycidyl methacrylate copolymer and ethylene-methyl acrylate-glycidyl methacrylate terpolymer in a mass ratio of 2:2:1; the antioxidant is obtained by combining antioxidant 1010, antioxidant 168 and antioxidant 1076 in a mass ratio of 1:1:1.

[0070] The rest of the preparation process, components, and proportions are the same as in Example 3.

[0071] Comparative Example 1: The difference between this comparative example and Example 4 is that the upper surface layer 1 and the lower surface layer 3 lack the component-modified epoxy barrier agent, while the rest are the same as Example 4.

[0072] Results Analysis

[0073] The modified epoxy barrier agent prepared in Example 4 of this invention was characterized by nuclear magnetic resonance. 1 HNMR images are shown Figure 2The peaks at 4.16 ppm and 3.92 ppm are proton peaks of the methylene group on the hexa-boron ester ring, the peak at 10.58 ppm is a proton peak of the sulfonamide group, and the peaks at 6.81 ppm and 7.62 ppm are proton peaks of the benzene ring. This indicates that 2-[(4,6-diamino-1,3,5-triazin-2-yl)amino]propane-1,3-diol reacted successfully with (4-(cyclopropanesulfonamide)phenyl)boronic acid. The peak at 5.37 ppm is a hydroxyl proton peak, and the peak at 2.66 ppm is a proton peak of the methylene and methine groups on the epoxy group. This proves that the intermediate was further reacted with diethylene glycol diglycidyl ether to prepare a modified epoxy barrier agent.

[0074] The cell density, compressive strength, oxygen permeability, and water vapor permeability of the multilayer polymer foam materials prepared in each example and comparative example were determined according to ASTM D3576, ASTM D3574, ASTM D3985, and ASTM E96 standards, respectively. Following ISO 14855-1, the samples were cut into 20mm × 20mm pieces and buried in a temperature-controlled composting environment (58±2℃, humidity 50-55%). The weight loss rate was measured at 45 and 90 days. The above measurements and results are shown in Table 1.

[0075] Table 1 Performance test results of multilayer polymer foam materials

[0076] Testing items Example 1 Example 2 Example 3 Example 4 Comparative Example 1 <![CDATA[Cell density (×10 5 cells / cm 3 )]]> 5.10 5.05 4.95 5.12 2.15 Compressive strength (kPa) 165 160 158 162 85 <![CDATA[Oxygen transmission rate (cm 3 / (m 2 ·d·atm))]]> 185 195 205 190 1250 <![CDATA[Water vapor transmission rate (g / (m 2 ·d))]]> 27 26 30 28 105 45-day composting weight loss rate (%) 28.5 26.8 27.1 28.8 32.2 90-day composting weight loss rate (%) 70.5 68.2 69.5 70.2 78.5

[0077] As can be seen from Table 1, the cell density of each embodiment was significantly improved, the cells became finer and more uniform, the compressive strength increased, and the barrier properties were greatly improved. They also showed good degradability in the composting environment. Compared with Comparative Example 1 without the addition of modified epoxy barrier agent, the difference in compost weight loss rate after 45 days and 90 days was small.

[0078] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

[0079] The present invention and its embodiments have been described above. This description is not restrictive, and the embodiments shown are only one of the embodiments of the present invention. The actual application is not limited to this. In conclusion, if those skilled in the art are inspired by this description and design similar methods and embodiments without departing from the spirit of the present invention, they should all fall within the protection scope of the present invention.

Claims

1. A biodegradable multilayer polymer foam material, characterized in that: It consists of an upper surface layer, a lower surface layer, and a core layer disposed between the upper surface layer and the lower surface layer. The upper surface layer and the lower surface layer comprise the following components in parts by weight: 50-80 parts PBAT, 20-50 parts PLA, 3-8 parts foaming agent, 5-15 parts modified epoxy barrier agent, 0.5-2 parts epoxy chain extender, 1-5 parts calcium silicate, 3-10 parts montmorillonite, 0.5-2 parts lubricant, and 0.2-1 parts antioxidant. The core layer comprises the following components in parts by weight: 40-70 parts PBAT, 30-60 parts PLA, 5-12 parts foaming agent, 0.5-2 parts epoxy chain extender, 1-5 parts calcium silicate, 3-10 parts montmorillonite, 0.5-3 parts talc, 0.5-2 parts lubricant, and 0.2-1 parts antioxidant; The modified epoxy barrier agent is prepared through the following steps: (1) Add 2-[(4,6-diamino-1,3,5-triazine-2-yl)amino]propane-1,3-diol and dry N,N-dimethylformamide to the reactor and stir until completely dissolved. Slowly add (4-(cyclopropanesulfonamide)phenyl)boric acid and catalyst a under a nitrogen atmosphere. Heat to 75-85℃ and react for 5-8 hours. After the reaction is complete, cool the mixture to room temperature, pour it into ice water to precipitate, filter, wash the precipitate with water, and dry it under vacuum to obtain the intermediate. (2) Add intermediate and dry dimethyl sulfoxide to the reactor, stir to dissolve, add excess diethylene glycol diglycidyl ether, stir to mix evenly, add catalyst b; heat to 90-100℃, react for 7-9 hours, after the reaction is completed, cool the reaction solution to 45-55℃, add ethanol to precipitate the product, filter, wash with ethanol, and obtain the modified epoxy barrier agent by vacuum drying. In step (1), the molar ratio of 2-[(4,6-diamino-1,3,5-triazine-2-yl)amino]propane-1,3-diol to (4-(cyclopropanesulfonamide)phenyl)boronic acid is 1:0.95-1.05; catalyst a is one of p-toluenesulfonic acid, camphorsulfonic acid, or tetraisopropoxytitanium, and its addition amount is 0.5%-2% of the total mass of the reactants; in step (2), the molar ratio of diethylene glycol diglycidyl ether to the intermediate is 2.2-2.8:1; catalyst b is one of triphenylphosphine, triethylamine, or benzyltriethylammonium chloride, and its addition amount is 1%-3% of the mass of the intermediate.

2. The biodegradable multilayer polymer foam material according to claim 1, characterized in that: The foaming agent is one of azodicarbonamide, sodium bicarbonate, or 4,4'-oxobis(benzenesulfonyl)hydrazine.

3. The biodegradable multilayer polymer foam material according to claim 1, characterized in that: The lubricant is one of zinc stearate, calcium stearate, or polyethylene wax.

4. The biodegradable multilayer polymer foam material according to claim 1, characterized in that: The epoxy chain extender is at least one of styrene-ethylene acrylate copolymer, glycidyl methacrylate copolymer, or ethylene-methyl acrylate-glycidyl methacrylate terpolymer.

5. The biodegradable multilayer polymer foam material according to claim 1, characterized in that: The antioxidant is at least one of antioxidant 1010, antioxidant 168, or antioxidant 1076.

6. The method for preparing the biodegradable multilayer polymer foam material according to any one of claims 1-5, characterized in that: Includes the following steps: S1. The components of the surface layer and the core layer are premixed evenly in a high-speed mixer according to the proportions. Then, they are melt-blended, extruded, cooled, and pelletized separately through a twin-screw extruder at a processing temperature of 140-170℃ to obtain surface layer masterbatch and core layer masterbatch. S2. Multilayer co-extrusion foaming: The surface masterbatch and core masterbatch are added to the corresponding hoppers of the three-layer co-extrusion foaming molding machine, wherein the upper and lower surface layers use surface masterbatch, and the core layer uses core masterbatch; the processing temperatures of each section are set as follows: Zone 1 150℃, Zone 2 160℃, Zone 3 165℃, and die head 170℃. After melt co-extrusion, foaming, shaping, traction, and cutting, the biodegradable multilayer polymer foam material is obtained.

Citation Information

Patent Citations

  • Method for obtaining a functionalized triazine compound and the triazine compound obtained by said method

    EP2774922A1

  • Waste polypropylene-modified foaming plate and manufacturing method thereof

    CN102218879A

  • Multilayer biodegradable foaming buffer film and preparation method thereof

    CN115139603A